Crosstalk in the Retinal Neurovascular Unit – Lessons for the Diabetic Retina - Feng, Y.; Busch, S.; Gretz, N.; Hoffmann, S.; Hammes, H.-P. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Diabetic retinopathy shares important features with neurodegenerative retinal diseases, including loss of ganglion cells and retinal thinning. The impact on vasoregression and subsequent ischemia-driven changes such as macular edema and proliferative retinopathy are not established. Studies using adult neurodegenerative animal models such as the transgenic TGR(CMV-PKD2(1/703)HA) rat imply early activation of the innate immunity system and the complement system as well as microglia playing a role in the damage of the retinal neurovascular unit.
Keywords: diabetes; oxidative stress; neuropathy; reknopathy